Convexity, Differential Equations, and Games - Sjur Didrik Flåm (Center for Economic Studies and ifo Institute (CESifo), 2002)
Theoretical and experimental studies of noncooperative games increasingly recognize Nash equilibrium as a limiting outcome of players repeated interaction. This note, while sharing that view, illustrates and advocates combined use of convex optimization and differential equations, the purpose being to render equilibrium both plausible and stable.
Keywords: 330; noncooperative games; Nash equilibrium; repeated play; differential equations; stability.